24. Season four [videorecording (DVD)] - Cassar, Jon, 1958-; Sutherland, Kiefer, 1966-; Surnow, Joel; Cochran, Robert (20th Century Fox Home Entertainment, 2005)
Many familiar faces return for this day of crisis. A fearsome new villain is played with cold-hearted intensity. The threat this time around is much different, and for Jack Bauer there are multiple situations to deal with. Jack has to make some extremely difficult choices, including how to handle a new love in his life who happens to be the daughter of the Secretary of Defense. Their new found love will be put to the ultimate test during the next 24 hours.